Investigating the Links Between Performers’ Self-Compassion, Mental Toughness and Their Social Environment: A Semi-Systematic Review - Kosirnik, Celine; Antonini Philippe, Roberta; Pomini, Valentino (Frontiers in Psychology, 2022)
Being mentally tough while evaluate oneself in a compassionate way is still a difficult path for performers. Self-compassion, characterized by the ability to be kind to oneself, to see one’s experiences as part of the larger human experience and have a balanced awareness to one's emotions and thoughts, was recently studied as a stepping stone to performance optimization and personal development. Despite a mistrust of this concept in the sports world, various studies show its benefits within athletes. A major question remains the environment that foster or hinder the development of self-compassion: when role models extend compassionate attitudes, does it allow performers to respond in more self-compassionate ways? The relationship between self-compassion, mental toughness and social environment is still unclear and is an important direction for future research within performers. This semi-systematic literature review aims at proposing an overview of the state of the art regarding self-compassion, mental toughness and the influence of performers' social environments. Sixteen studies were retrieved. We conclude that the number of multi-day intervention programs and longitudinal studies should be increased. The studies should also consider assessing the specific aspects of performance culture and settings. In addition, overall performance specific measures could be developed to assess general levels of self-compassion. The development of a theoretical framework explaining how self-compassion affects a performer, the role of their entourage and its link to other psychological resources, such as mental toughness, could help to better understand this concept.